Evaluation of safety of caesarean myomectomy: A prospective study - Nargis, Nazlima; Karim, Md Iqbal; Loverine, Salma (Bangladesh Critical Care Journal, 2019)
Background: Uterine myomas are the most common benign tumour of female reproductive tract and the prevalence of myomas in pregnancy has been reported to be 2%to 5% . Myomectomy during cesarean section has traditionally been discouraged due to risk of intractable haemorrhage and fear of hysterectomy. But recently large scaled studies indicated that cesarean myomectomy could be safely performed in majority of cases without any serious or life threatening complications. Materials and Methods: This prospective study was done at Ibn Sina Medical College Hospital, Dhaka, Bangladesh between January 2016 and December 2016. Fifty patients were recruited into the study, 25 patients had undergone myomectomy during cesarean section and 25 patients had undergone only cesarean section. Results: Average value of haemoglobin both pre and post-operatively was 12.31±1.22 g/dl and 10.64±1.51 g/dl for patients who had cesarean section with myomectomy and 11.61±1.3 g/dl and 10.3±1.7 g/dl in the other group in which cesarean section without myomectomy was performed. The difference in average haemoglobin for patients who had a cesarean section and myomectomy was 1.41 while those who had caesarean section alone was 1.32±1.12. This was not significant. The average duration of operation was longer in patient who had cesarean section and myomectomy (54.32±18.06 mins) than those who had caesarean section alone (38.54±8.42mins). The incidence of hemorrhage was5.45±1.23% and 5.23±1.03% respectively and the mean length of postoperative hospitalization was2.42±1.45and 2.17±0.70 days and no hysterectomy was needed in any group. Blood transfusion was given in 6 patients with 3 patients in each group. Sixty eight percent of the fibroids were subserous and in the body of the uterus. Conclusion: Cesarean myomectomy is a safe and effective procedure and does not increase the incidence of intraoperative and postoperative complications. Bangladesh Crit Care J March 2019; 7(1): 40-43